(untitled) (Indian Journal of Case Reports, 2020)
Children have a habit of placing various objects in their mouths as a part of normal development. Accidental ingestion or embedment of the object in hard and soft tissues of the oral cavity is commonly encountered. A thorough history and clinical and radiographic examination aid in the diagnosis and treatment planning in such cases. The present article describes foreign body impaction in the primary tooth of a young child and its successful management along with a review of literature highlighting cases of foreign objects in primary dentition and their retrieval.